AERATION AND MASS TRANSFER UNDER CULTIVATION OF FODDER YEAST - Obodovich, A.; Ivanitskii, G.; Borhalenko, Y.; Sidorenko, V. (Energy and Automation, 2016)
The research on the effect of setting the frequency of the pulsations in the rate of mass transfer of oxygen in the process of fodder yeast DDGS during its processing by discrete pulse energy input.